Electronic structure and orientation of benzene adsorbed on a pseudomorphic Cu monolayer on Ru(0001) - Koschel, Herbert; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2000)
The adsorption of benzene on a pseudomorphic Cu monolayer on Ru(0001) was studied by temperature-programmed desorption and angle-resolved UV photoelectron spectroscopy in combination with symmetry selection rules. Benzene is molecularly adsorbed on the pseudomorphic Cu monolayer on Ru(0001). Desorption of the first layer occurs in the temperature range between 155 and 340 K. In contrast to the clean Ru(0001) surface, no decomposition is observed upon heating. The analysis of the binding energies of the molecular benzene levels reveals a significant bonding shift of 1.1 eV of the benzene π levels, which is nearly as large as the value of 1.4 eV for the strongly chemisorbed saturated benzene layer on Ru(0001). The benzene molecules are azimuthally oriented with the C-H bonds aligned along the [101̄0] direction. This geometry corresponds to an azimuthal rotation of 30° as compared to that on the clean Ru(0001) surface.